Dissecting disease, race, ethnicity, and socioeconomic factors for hepatocellular carcinoma: An analysis from the United States Safety Net Collaborative. (December 2020) - Lee, Rachel M.; Gamboa, Adriana C.; Turgeon, Michael K.; Yopp, Adam; Ryon, Emily L.; Kronenfeld, Joshua P.; Goel, Neha; Wang, Annie; Lee, Ann Y.; Luu, Sommer; Hsu, Cary; Silberfein, Eric; et al.
Abstract: Background: Racial/ethnic and socioeconomic disparities are assumed to negatively affect treatment and outcomes for hepatocellular carcinoma (HCC). Our aim was to investigate the interaction of racial/ethnic and socioeconomic factors with stage of disease and type of treatment facility in receipt of treatment and overall survival (OS) of patients with HCC. Methods: All patients with primary HCC in the US Safety-Net Collaborative database (2012–2014) were included. Patients were categorized into "safety-net" or "tertiary referral center" based on where they received treatment. Socioeconomic factors were determined at the zip-code level and included median income and percent of adults who graduated from high-school. Primary outcomes were receipt of treatment and OS. Results: On MV Cox regression, neither race/ethnicity, median income, nor care provided at a SNH were associated with decreased OS (all p > 0.05). Independent predictors of decreased OS included lack of insurance (HR 1.34), less educational attainment (HR 1.59) higher MELD score (HR 1.07), higher stage at diagnosis (II:HR 1.34, III:HR 2.87, IV:HR 3.23), and not receiving treatment (HR 3.94) (all p < 0.05). Factors associated with not receiving treatment included history of alcohol abuse (OR 0.682), increasing MELD (OR 0.874), higher stage at diagnosis (III: OR 0.234, IV: OR 0.210) and care at a safety net facility (OR 0.424) There were no racial/ethnic or socioeconomic disparities in receipt of treatment. Conclusions: There is no intrinsic or direct association of race/ethnicity, socioeconomic status, or being treated at select safety-net hospitals with worse outcomes. Poor liver function, no insurance, and advanced stage of presentation are the main determinants of not receiving treatment and decreased survival. Highlights: Racial and socioeconomic disparities are assumed to negatively affect treatment and outcomes. Using a multi-institutional database, we investigated how these factors affect care for HCC. We found no link between race, socioeconomics, or care at a safety-net hospital and worse outcomes.